Media Scrapbook: Alternatif Kreatif dalam Pembelajaran Matematika Bangun Ruang di Madrasah Ibtidaiyah - Yhasinta Agustyarini; Aristia Hidayah; Suci Wulan Sari; Nurul Azizah Ria Kusrini (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Learning mathematics on the topic of spatial figures is still a challenge for elementary school students because it requires high visualization skills. One solution to overcome these difficulties is to present innovative and interactive learning media. This study aims to develop scrapbook learning media on spatial geometry material, as well as to test its feasibility, student and teacher responses, and its effectiveness in improving learning outcomes. The method used is research and development (R&D) with a simplified ADDIE model. The subjects of the study were 20 fourth-grade students of Madrasah Ibtidaiyah. The instruments used included expert validation sheets, student and teacher response questionnaires, learning outcome tests, observation, and documentation. The results showed that the scrapbook media was declared very feasible with an average expert validation score of 86%. Student responses were in the very good category with a percentage of 89.6%. Teacher responses were in the very good category with a percentage of 92%. In addition, there was an increase in learning outcomes from the average pretest score of 40.05 and the average posttest of 76.90, with an average N-Gain of 0.6090 or 60.90%. The conclusion of this study is that scrapbook media is effective for use as an alternative mathematics learning media, because it is able to increase students' interest, motivation, and learning outcomes in spatial geometry material